2014
DOI: 10.3141/2458-04
|View full text |Cite
|
Sign up to set email alerts
|

Method for Road Lighting Audit and Safety Screening at Urban Intersections

Abstract: The review of recent research efforts in road lighting and safety shows an inconsistency in the methods to measure ambient road lighting. The importance of road lighting on improving night time safety is evident; however, the lack of actual illuminance field measurements results in a gap in the knowledge of whether installed road lighting provides adequate illuminance for clear visibility at night time or not. Previous studies considered the presence or absence of road lighting on safety without measuring actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Illuminance measurements are another frequently performed measurement. These measurements make it possible to determine the indoor [11][12][13] and outdoor [14][15][16][17] lighting condition. Determining the illuminance distribution enables us to determine the main criterion values (the average illuminance and illuminance uniformity) given in the standardization requirements.…”
Section: Introduction 1photometric Measurementsmentioning
confidence: 99%
“…Illuminance measurements are another frequently performed measurement. These measurements make it possible to determine the indoor [11][12][13] and outdoor [14][15][16][17] lighting condition. Determining the illuminance distribution enables us to determine the main criterion values (the average illuminance and illuminance uniformity) given in the standardization requirements.…”
Section: Introduction 1photometric Measurementsmentioning
confidence: 99%
“…It has been also observed that increased intensity of road lighting decreases the number of accidents with pedestrian of 59%. Similarly, increased intensity of roadway lightning and installation of flashing warning signs acts with a reduction of pedestrian crashes of 57% in nighttime and a significant decrease in daytime, about 21%(Zgeer et al, (2006);Nassar et al, (2011);Scott et al, (2012);Bassani et al, (2012);Niaki et al, (2014);Bichicchi et al, (2017);Gibbons at al., (2015);Wei et al, (2016); Bullough et al, (2017 Bullough et al, ( ), (2021;Wang et al, (2018);Gbologah et al, (2019);Bhagavathula et al, (2019Bhagavathula et al, ( ), (2020;Costa et al, (2017), (…”
mentioning
confidence: 99%
“…The safety of the night-time navigation task by drivers can be significantly improved with the provision of lighting, especially at intersections, where density of crashes tends to be typically higher than other sections of the roadway. Intersection lighting is a proven safety countermeasure as evidenced by multiple studies ( 2 7 ). In a comparative analysis of 376 illuminated and unilluminated rural and near-urban intersections, Bruneau and Morin found that nonstandard lighting and standard lighting can reduce night-time accident rates by 29% and 39%, respectively ( 7 ).…”
mentioning
confidence: 99%